2019
DOI: 10.18203/2349-2902.isj20193165
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in patients of diabetes mellitus: a cross sectional study

Abstract: Background: One of the independent risk factor for erectile dysfunction is diabetes mellitus. The present study planned to determine the prevalence and factors associated with ED in DM.Methods: A one year cross-sectional study on a total of 208 patients with type 1 or 2 diabetes. National Institutes of Health (NIH) approved questionnaire for International Index of Erectile Function (IIEF) was used to interview each patient to assess for ED.Results: In this study 12.98% of patients had ED score between 13 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Mean age of participants with SD was also higher, 46.14 ± 3.78 years, as compared to 41.12 ± 5.19 years in participants with no SD. Similar to our study, Bellad and Sahu [14] concluded that mean age in patients with SD was significantly high (58.40 ± 10.96 years) as compared to those without SD (51.00 ± 11.16 years). Our observation was also consistent with studies of Rutte et al [15] and Tuncel et al [16]…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mean age of participants with SD was also higher, 46.14 ± 3.78 years, as compared to 41.12 ± 5.19 years in participants with no SD. Similar to our study, Bellad and Sahu [14] concluded that mean age in patients with SD was significantly high (58.40 ± 10.96 years) as compared to those without SD (51.00 ± 11.16 years). Our observation was also consistent with studies of Rutte et al [15] and Tuncel et al [16]…”
Section: Discussionsupporting
confidence: 94%
“…Mean age of participants with SD was also higher, 46.14 ± 3.78 years, as compared to 41.12 ± 5.19 years in participants with no SD. Similar to our study, Bellad and Sahu [14] concluded that mean age in patients with SD was significantly high (58.40 ± 10.96 years) as compared to those without SD (51.00 ± 11.16 years). Our observation was also consistent with studies of Rutte et al [15] and Tuncel et al [16] The prevalence of SD among female group and male group with longer (>10 years) duration of diabetes was 88% and 91.7%, respectively, as compared to 70.35% and 58.97%, respectively, in 5-10-year duration group and 31.09% and 23.25%, respectively, in < 5-year duration group.…”
Section: Discussionsupporting
confidence: 91%
“…Erectile dysfunction (ED) is a significant medical condition that impairs sexual performance and affects self-esteem, ultimately leading to marital difficulties. In 1995, more than 152 million men throughout the world suffer from erectile dysfunction, and this figure is anticipated to climb to 322 million by 2025 [2]. Chronic hyperglycemia with changes in carbohydrate, lipid, and protein metabolism are hallmarks of diabetes mellitus, which is caused by a defect in insulin production or action, or both [3,4] About 26 million Americans have diabetes, according to the Centers for Disease Control & Prevention (CDC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…A study found that smoking cigarettes was an independent risk factor for heart disease. ED was shown to be significantly more common among males who were included in trials with more than 6000 participants [2].…”
Section: Introductionmentioning
confidence: 99%